ANALISIS PERBANDINGAN EFISIENSI BANK UMUM SYARIAH (BUS) DAN UNIT USAHA SYARIAH (UUS) DENGAN METODE DATA ENVELOPMENT ANALYSIS - Khairunisa Sinatriana (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
Bank Umum Syariah (full fledged Islamic bank) and Unit Usaha Syariah (full branch Islamic bank) are financial institutions that has been developed at this time. It has been proven by the increasing number of Islamic Banks branch offices in Indonesia, as well as total assets increased in Islamic Banks (BUS and UUS). However, the market share of Islamic banking represents only 5% of the total assets of banks nationwide. The aim of this study is to analyze the comparison of efficiency between Bank Umum Syariah (BUS) and Unit Usaha Syariah (UUS) in Indonesia in 2011-2015 by using Data Envelopment Analysis (DEA). The level of efficiency is a measurement of the performance of Islamic banking in the use of the existing input and can generate maximum output. Input variables used in this research are Total Assets, Third Party Fund (FPT), and Operating Costs. While for the output variables used are the Financing and Operating Income. This research is quantitative. Sampling technique used in this research is purposive sampling. The number of samples in this research are 5 Bank Umum Syariah and 5 Unit Usaha Syariah. Data analysis technique used the method of Data Envelopment Analysis. The results showed that the level of efficiency of the development trend of Islamic Banks in Indonesia in the years 2011-2015 was fluctuating, while the level of efficiency of the development trend of Sharia in the years 2011-2015 was positive or increased. However, for comparative degree of efficiency between BUS and UUS, found no significant differences between the two of them.